Struktur batuan pascalongsor menggunakan metoda geolistrik tahanan jenis konfigurasi Wenner (The post-landslide rock structure uses the Wenner configuration resistivity geoelectric method ) - - Nizamullah; - Akmam; - Syafriani (PILLAR OF PHYSICS, 2018)
Malalak was located in Sumatra active fault segment that Sianok Segment. This condition caused Malalak prone to landslide hazard. Landslides a natural disasters which can lead to loss of either life or property. Based on local conditions, it  need to do  research the geological rock types making up Malalak. The objective this research was to find resistivity and structure of rock. The research that used was basic research descriptively. Measurements were made using the Geoelectrical resistivity method Wenner configuration. The interpretation of the data was used Software Res2dinv to get resistivity  and depth of rocks in 2D model cross section below the earth surface. Result of this research indicated the type of rocks in Malalak were Clay, Porphyrite, Limestone, Andesite, and Granite. Resistivity approach was derived from the five tracks were, Clay haved resistivity 9,93 Ωm – 77,3 Ωm, Porphyrite 77,4 Ωm – 216 Ωm, Limestone 216,1 Ωm – 1050 Ωm, Andesite 1050,1 Ωm – 3533 Ωm and Granite 3533,1 Ωm – 5217 Ωm.